2021
DOI: 10.3390/su13042326
|View full text |Cite
|
Sign up to set email alerts
|

The Green Accommodation Management Practices: The Role of Environmentally Responsible Tourist Markets in Understanding Tourists’ Pro-Environmental Behaviour

Abstract: The green accommodation sectors are increasingly committed to implementing environmental management practices while enhancing guests’ pro-environmental behaviour. However, it is not easy to change tourists’ behaviour as there are many factors influencing tourists’ participation in green management actions. This paper argues that a combination of multiple factors such as visitor characteristics or previous environmental experience needs to be examined to determine how these factors are differently associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In that case, low-carbon hotels can make long-term profitability. Accordingly, the manager needs to focus on GPEB [16,24]; hotels must know about guests' GPEB demands so that they can provide suitable service and achieve tourist satisfaction and loyalty [43,104,149]. Thus, the study of GPEB needs to be associated with low-carbon service and business performance.…”
Section: Guests' Pro-environmental Behaviormentioning
confidence: 99%
“…In that case, low-carbon hotels can make long-term profitability. Accordingly, the manager needs to focus on GPEB [16,24]; hotels must know about guests' GPEB demands so that they can provide suitable service and achieve tourist satisfaction and loyalty [43,104,149]. Thus, the study of GPEB needs to be associated with low-carbon service and business performance.…”
Section: Guests' Pro-environmental Behaviormentioning
confidence: 99%
“…Early childhood pre-service teacher is a subject that provides education to young children who need to understand the concept of zero waste. Some zero-waste topics related to education in schools include waste processing, waste recycling, and reducing the use of plastic bags (Hoffmann & Muttarak, 2020;Kim et al, 2021;Listyarini et al, 2019;Meloni et al, 2019;Nkaizirwa et al, 2022). Early childhood pre-service teachers must have good attitudes and behavior related to protecting the environment on the topic of zero waste.…”
Section: Resultsmentioning
confidence: 99%
“…Previous travel and tourism studies have focused on environmental concerns of tourists in influencing their intention to act in a more environmental way when they travel (Aman et al, 2021;Gansser and Reich, 2023;Kim et al, 2021;O'Connor and Assaker, 2021;Ribeiro et al, 2023). For instance, Kim et al (2021) and Aman et al (2021) both found that environmental concerns positively influence the pro-environmental behavior of tourists staying at green accommodations in Australia as well as international tourists visiting Pakistan. More recently, Ribeiro et al (2023) also showed that pro-environmental concerns Figure 1 The proposed model exerted a positive influence on the green travel behavior of UK residents when traveling abroad in this case (see Ribeiro et al, 2023).…”
Section: Sustainability Concerns and Social Norms On Sustainable Trav...mentioning
confidence: 99%
“…While previous research on sustainable tourism has already examined the effects of various factors on tourists’ STB, these studies have focused primarily on the environmental aspects of sustainability (Gansser and Reich, 2023; Kim et al , 2021; Pearce et al , 2022; Ribeiro et al , 2023). Even though these studies clearly identify environmental concern, social norms or others’ opinions as key determinants of tourists’ pro-environmental travel behavior (D’Arco et al , 2023), very few have examined tourists’ sustainable behavior in general (see Pinho and Gomes, 2023; Salinero et al , 2022), further failing to extend the combined effects of the aforementioned variables identified both in the specific context of pro-environmental travel to the general context of tourists’ STB.…”
Section: Introductionmentioning
confidence: 99%